Membangun Inklusi Gender dalam Praktik Manajemen Sumber Daya Insani - Ghulam Asy Sya’Bany; Ummul Karomah (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2024)
: This article discusses the importance of gender inclusion in human resource management practices to create a fair, productive, and sustainable work environment. This study aims to identify effective strategies to overcome challenges in implementing gender inclusion, such as gender stereotypes, unconscious bias, and inflexible organizational structures. The study was conducted using a qualitative method with a case study approach in several companies in Indonesia that have implemented gender inclusion practices. The results of this study also show that gender inclusion improves innovation, productivity, and organizational performance through diverse perspectives in decision-making. This article provides policy recommendations, such as bias awareness training, inclusive recruitment policies, and job insecurity. Thus, this study not only supports social justice but also offers strategic advantages for organizations in facing the dynamics of a complex and diverse work world.